2016
DOI: 10.1093/gbe/evw259
|View full text |Cite
|
Sign up to set email alerts
|

Comparative “Omics” of theFusarium fujikuroiSpecies Complex Highlights Differences in Genetic Potential and Metabolite Synthesis

Abstract: Species of the Fusarium fujikuroi species complex (FFC) cause a wide spectrum of often devastating diseases on diverse agricultural crops, including coffee, fig, mango, maize, rice, and sugarcane. Although species within the FFC are difficult to distinguish by morphology, and their genes often share 90% sequence similarity, they can differ in host plant specificity and life style. FFC species can also produce structurally diverse secondary metabolites (SMs), including the mycotoxins fumonisins, fusarins, fusar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
133
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(140 citation statements)
references
References 128 publications
(201 reference statements)
7
133
0
Order By: Relevance
“…LTR elements are the most abundant TEs in C. higginsianum , as reported in other fungi, e.g. Cochliobolus heterostrophus , F. fujikuroi , F. oxysporum , L. maculans and V. dahliae [94–97] and several Colletotrichum species [13, 91]. Most of the DNA transposons in C. higginsianum belong to the TIR order, superfamily Tc1-Mariner.…”
Section: Discussionmentioning
confidence: 81%
“…LTR elements are the most abundant TEs in C. higginsianum , as reported in other fungi, e.g. Cochliobolus heterostrophus , F. fujikuroi , F. oxysporum , L. maculans and V. dahliae [94–97] and several Colletotrichum species [13, 91]. Most of the DNA transposons in C. higginsianum belong to the TIR order, superfamily Tc1-Mariner.…”
Section: Discussionmentioning
confidence: 81%
“…purpurea and F . fujikuroi clusters (Hinsch et al ., ; Niehaus et al ., ), cytochrome P450 monooxygenase‐encoding genes adjacent to IPT‐LOGs were observed for all analysed Fusarium strains. However, phylogenetic analysis of cytochrome P450 monooxygenases suggested that, like IPT‐LOG, there were three sequence types (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…purpurea (CPUR_04177) and two in F . fujikuroi (FFUJ_03536 and FFUJ_14354) were shown to contribute to a large proportion of the tZ pool produced by these species (Hinsch et al ., ; Niehaus et al ., ). This prompted an analysis of a broader suite of fungal genomes for sequence homologues of these genes.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations